2018
DOI: 10.1080/02699052.2018.1495339
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship and clinical management between traumatic brain injury and pain in military and civilian populations

Abstract: In this review, we discuss the comorbidity of traumatic brain injury (TBI) and pain among civilians and military members, the common causes of pain resulting from TBI, and offer insight about the therapeutic management of TBI symptoms and pain. Traumatic brain injury (TBI) is a debilitating health problem and one of the most common post-TBI symptoms is pain, which can contribute to psychological issues such as Post-traumatic stress disorder (PTSD) and depression. Headache pain appears to be the most common typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…One multi-center study found that over 70% of people receiving acute rehabilitation after TBI were prescribed opioids during their hospital stay (Hammond et al, 2015). Persons with persistent post-concussive symptoms after TBI are also more likely to be prescribed opioids (Mehalick & Glueck, 2018;Seal et al, 2018). In addition to the known addictive properties of long-term opioid therapy (Chou et al, 2015;Dowell, Haegerich, & Chou, 2016), individuals with TBI may be more susceptible to OUD compared to those without a history of brain injury.…”
mentioning
confidence: 99%
“…One multi-center study found that over 70% of people receiving acute rehabilitation after TBI were prescribed opioids during their hospital stay (Hammond et al, 2015). Persons with persistent post-concussive symptoms after TBI are also more likely to be prescribed opioids (Mehalick & Glueck, 2018;Seal et al, 2018). In addition to the known addictive properties of long-term opioid therapy (Chou et al, 2015;Dowell, Haegerich, & Chou, 2016), individuals with TBI may be more susceptible to OUD compared to those without a history of brain injury.…”
mentioning
confidence: 99%
“…19 If a blast-related, mild TBI injury occurs, accompanying problems with head, neck, or back pain, or a combination of these, may emerge. 20 It is vitally important for primary care providers to complete a veteran-centric military health history because the potential for a TBI during training or deployment is high. TBI can mimic a variety of conditions.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“… Indeed, the only published trial of behavioral treatment for PTH found no benefit in a civilian sample. Veterans with PTH may respond to treatment differently than civilians owing to a higher risk of comorbid PTSD symptoms, but at the time of this article, there are no published randomized clinical trials in veterans for any PTH intervention.…”
Section: Introductionmentioning
confidence: 99%